2001
DOI: 10.1016/s0042-6989(00)00242-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived motion in orientational afterimages: direction and speed

Abstract: Two sets of experiments demonstrate new properties of motion in orientational after-effects. In a previous report, we showed that when observers adapted to a static bar grating whose elements varied in size or intensity from one side to the other, offset of the grating resulted in a motion after-effect, with the perceived motion in the direction of the largest or most intense bar. In the first new experiment, we show that similar results can be produced by varying the duration of the bar elements, with the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Consequently, the smear that trails a moving object will lengthen. This trace or motion smear invariably accompanies motion and previous studies have demonstrated the contribution of the motion trail to the detection of motion (Barlow & Olshausen, 2004; Burr & Ross, 2002; Edwards & Crane, 2007; Geisler, 1999; Ross, Badcock, & Hayes, 2000) and to the perception of speed (Francis & Kim, 2001; Ross, 2004). Additionally it has been shown that cells at the V1 cortex of cats and monkeys and superior temporal sulcus (STS) of monkeys, and the human motion complex (MT+) are sensitive to motion streak information (Geisler, Albrecht, Crane, & Stern, 2001; Jancke, 2000; Krekelberg et al, 2003; Krekelberg, Vatakis, & Kourtzi, 2005).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consequently, the smear that trails a moving object will lengthen. This trace or motion smear invariably accompanies motion and previous studies have demonstrated the contribution of the motion trail to the detection of motion (Barlow & Olshausen, 2004; Burr & Ross, 2002; Edwards & Crane, 2007; Geisler, 1999; Ross, Badcock, & Hayes, 2000) and to the perception of speed (Francis & Kim, 2001; Ross, 2004). Additionally it has been shown that cells at the V1 cortex of cats and monkeys and superior temporal sulcus (STS) of monkeys, and the human motion complex (MT+) are sensitive to motion streak information (Geisler, Albrecht, Crane, & Stern, 2001; Jancke, 2000; Krekelberg et al, 2003; Krekelberg, Vatakis, & Kourtzi, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…Experiments three and four were designed to investigate motion smear as a possible underlying cause of the speed overestimation illusion under low levels of luminance. The visible trail that follows a moving object lengthens at higher speeds, and so has potential as a cue to speed (Francis & Kim, 2001; Ross, 2004). Interestingly, smear also lengthens with increased persistence and increased persistence is a hallmark of low luminance (Di Lollo & Bischof, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of illusory motion, in contrast, a perceptual impression of motion arises from spatio-temporal aspects of the stimulus itself or from the immediate, past history of viewing actual motion or intensity modulated, static images (e.g. Francis and Kim, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the overall design of the BCS, this rebound activity acts as a reset signal to curtail persisting neural signals. The properties of this gated dipole have been used to account for many properties of dynamic vision, including visual persistence (Francis, 1999;Francis et al, 1994) and motion perception (Francis & Grossberg, 1996b;Francis & Kim, 1999, 2001Kim & Francis, 1998, 2000. Neurophysiologicalevidence has been found for gated dipoles in general (Abbot, Varela, Sen, & Nelson, 1997) and for an orientation-based gated dipole in particular (Ringach, Hawken, & Shapley, 1997).…”
Section: Facade Theorymentioning
confidence: 99%